Determinants of the Maqashid Syariah Index of Islamic Banks: Implications on Social and Environmental Sustainability - Nurun Nadia; Muhammad Muflih; Ruhadi (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
Islamic banking holds a strategic role in promoting social and environmental sustainability through the implementation of Islamic economic principles. This study aims to analyze the factors influencing the Maqashid Sharia Index in Islamic banks in Indonesia and to examine its implications on multidimensional sustainability. The independent variables in this study are the Zakat Performance Ratio (ZPR) and Qardhul Hasan (QH) financing, with control variables consisting of Return on Assets (ROA) and Non-Performing Financing (NPF). The study employs panel data from Islamic banks in Indonesia over the period 2019–2023, selected using purposive sampling techniques. The data are analyzed using panel regression with the Random Effect Model (REM) approach. The findings indicate that ZPR, QH, ROA, and NPF have a positive and significant partial effect on the Maqashid Sharia Index. These results suggest that simultaneously optimizing social functions and financial performance is crucial for enhancing the contribution of Islamic banks to achieving sustainable Sharia objectives. This approach offers a fresh perspective on evaluating Islamic banking performance,not only in terms of profitability but also in how effectively institutions contribute to the comprehensive realization of Maqashid al-Sharia. Perbankan Syariah memiliki peran strategis dalam menciptakan kesejahteraan sosial dan keberlanjutan lingkungan melalui prinsip-prinsip ekonomi islam. Tujuan utama penelitian ini untuk menganalisis faktor-faktor yang mempengaruhi Indeks Maslahat pada Perbankan Syariah Indonesia serta mengkaji implikasinya terhadap keberlanjutan sosial dan lingkungan. Variabel independent pada penelitian ini yaitu Zakat Performance Ratio (ZPR) dan pembiayaan Qardhul Hasan (QH). Penelitian ini menggunakan data dari 9 Bank Umum Syariah di Indonesia dalam rentang waktu 2019-2023, yang dipilih melalui Teknik purposive sampling. Data tersebut dianalisis menggunakan regresi data panel, dengan model estimasi yang diterapkan adalah Random Effect Model (REM). Hasil penelitian mengungkapkan bahwa ZPR dan QH, baik secara simultan maupun parsial, berpengaruh positif dan signifikan terhadap Indeks Maslahat dalam Perbankan Syariah di Indonesia. Hasil temuan ini menegaskan bahwa perbankan syariah tidak hanya berfokus pada profitabilitas, tetapi juga memiliki peran dalam tanggung jawab sosial dan lingkungan yang perlu dioptimalkan. Oleh karena itu, diperlukan strategi kebijakan yang lebih progresif dalam mengelola ZPR dan QH agar perbankan Syariah semakin berdaya guna dalam menciptakan keseimbangan antara ekonomi, sosial, dan lingkungan secara berkelanjutan.